2007
DOI: 10.1038/sj.bjc.6603592
|View full text |Cite
|
Sign up to set email alerts
|

A human cancer-associated truncation of MBD4 causes dominant negative impairment of DNA repair in colon cancer cells

Abstract: MBD4 binds to methylated DNA and acts as a thymine DNA glycosylase in base excision repair. Deficiency of MBD4 in mice enhances mutation at CpG sites and alters apoptosis in response to DNA damage, but does not increase tumorigenesis in mismatch repair-deficient mice. However, in humans, frameshift mutation of MBD4, rather than deletion, is what occurs in up to 43% of microsatellite unstable colon cancers. There is no murine equivalent of this mutation. We now show that recombinant truncated MBD4 (MBD4 tru ) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…Interestingly, the inhibitory action of MBD was observed in both a cis-and trans-manner. This observation is different from a previously published study, 14 possibly because of a difference in the composition of the MBD4 tru and/or the substrate. However, our data are supported by a more recently published study which demonstrated that the efficiency of MED1 glycosylase activity was partially dependent on the extent of methylation of the DNA substrate.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Interestingly, the inhibitory action of MBD was observed in both a cis-and trans-manner. This observation is different from a previously published study, 14 possibly because of a difference in the composition of the MBD4 tru and/or the substrate. However, our data are supported by a more recently published study which demonstrated that the efficiency of MED1 glycosylase activity was partially dependent on the extent of methylation of the DNA substrate.…”
Section: Discussioncontrasting
confidence: 56%
“…A MBD containing truncated MED1 protein has been postulated to act in a dominant negative fashion to inhibit the activity of full length MED1. 14 We studied this effect on methylated G:IU substrate using equimolar concentrations of recombinant purified MBD the action of the GD on G:IU mispairs located in unmethylated, hemimethylated and fully methylated contexts. 5 In the current study, we measured the relative activity of full length MED1 on G:IU mispairs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Truncated Mbd4 proteins lack dominant negative effects. Because truncated MBD4 protein arising from residual expression of exons 1 to 3 or exons 1 to 5 could potentially act as dominant negative mutants (33) and inhibit CSR, we analyzed the pattern of Mbd4 transcription in control and Mbd4 KO cells. Although microarray analyses indicate that the transcript abundance of Mbd4 exons 1 to 3 is invariant, longer transcripts are severely reduced, beginning at exon 4, for the Mbd4 KO relative to controls ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo experiments also indicated that MBD4 can mediate the cellular response to DNA damage [19][20][21] and act as a candidate tumor suppressor gene [7].…”
Section: Introductionmentioning
confidence: 96%